Intentions and Realities in Doctoral Education in Norway. New Policies for Doctoral Education in Norway and the Implications for an Inter-Institutional Research School (WNGER II)—Some Preliminary Findings - Krumsvik, Rune Johan (Frontiers in Education, 2022)
This policy and practice review article examines how new policies and policy documents impact a research school, Western Norway Graduate School of Educational Research II (WNGER II) in Norway on general level. WNGER II is a research school consortium with seven universities and university colleges, six PhD-programmes, 97 PhD candidates and 48 supervisors. It was established in 2018 to complement PhD programmes and strengthen PhD education in Western Norway. Against this backdrop, this policy and practice review article builds on our previous research on doctoral-level education and aims to illuminate the more general learning and teaching conditions in the WNGER II consortium in light of national PhD regulations. This subject will be examined in light of the relationships among the arenas of formulisation (macro-level), transformation (meso-level) and realisation (micro-level). The frame factor theory is used as a lens to examine how new policies impact the doctoral level in higher education, and the main data source of the study is document analysis. The policy and practice review shows that the new national policies in doctoral education add a new layer of requirements on several levels, which can be demanding and challenging for institutions and might sometimes be considered part of what have come to be known as certain ‘public management’ tendencies in higher education. Such changing frame factors can also enhance the focus on educational quality, study quality and teaching quality at the doctoral level in WNGER II. For some institutions, it seems especially fruitful to handle the challenges with collaborative measures, such as research schools and so forth. A general tendency seems to be that, if WNGER II is going to optimise its potential as a collaborative research school, there should be increased integration among its six different PhD programmes. The study finds that certain actionable recommendations could be relevant to consider for the institutions’ frame factors for further development of the research school. There are also several limitations in the study, since this is the first phase of the formative dialogue research and only deals with a general policy review. Therefore, one has to interpret findings with great caution.